Our Literal Speed (The sixteenth century journal, 2019)
The article discusses the use of art to depict changes in early modern society. It mentions two print series by Flemish painter Pieter Bruegel the Elder of sailing ships, the question of risk as depicted by the ships, and the history of Antwerp, Belgium, and its role in shipping.